2021
DOI: 10.1136/emermed-2020-210688
|View full text |Cite
|
Sign up to set email alerts
|

Could a D-dimer/fibrinogen ratio have a role in ruling-out venous thromboembolism?

Abstract: BackgroundDiagnosis of venous thromboembolism (VTE) requires chest CT angiography for pulmonary embolism and venous ultrasound for deep vein thrombosis. To reduce imaging, guidelines recommend D-dimer levels to rule-out VTE in patients with a low pre-test probability. The most widely used D-dimer cut-off is 500 ng/mL. This cut-off has low specificity, meaning many patients without disease require imaging.MethodsIn this retrospective chart review, we evaluated the diagnostic performance of the D-dimer/fibrinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, raised D-dimer correlates with reduced pulmonary perfusion in patients hospitalized with COVID-19 (ref. 46 ) and venous thromboembolism is thought to be associated with raised D-dimer but normal fibrinogen 47 , which would explain why this mechanism is captured by a separate dimension of covariation. It is plausible that COVID-19-induced pulmonary embolisms (PEs) lead to cerebral hypoxia which in turn leads to a subtle degree of cognitive impairment, which is subjectively evident but not easily objectively measured (as subjective cognitive deficit can be a sensitive sign of early decline) 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, raised D-dimer correlates with reduced pulmonary perfusion in patients hospitalized with COVID-19 (ref. 46 ) and venous thromboembolism is thought to be associated with raised D-dimer but normal fibrinogen 47 , which would explain why this mechanism is captured by a separate dimension of covariation. It is plausible that COVID-19-induced pulmonary embolisms (PEs) lead to cerebral hypoxia which in turn leads to a subtle degree of cognitive impairment, which is subjectively evident but not easily objectively measured (as subjective cognitive deficit can be a sensitive sign of early decline) 48 .…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer to fibrinogen ratio (DFR) is a valuable predictor of PE, and combining D-dimer with fibrinogen can enhance the specificity of D-dimer and improve accuracy [ 7 , 14 ]. Studies have demonstrated the value of DFR in predicting PE in patients in the emergency department [ 15 , 16 ]. Anyway, the diagnostic value of DFR in postpartum women suspected of having PE still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, plasma TnI is usually used as a common diagnostic index in clinical APE, which can evaluate the severity of cardiopulmonary function damage. D-dimer/fibrinogen ratio ( 7 ) can be used as an active index of thrombosis. At present, it is widely used in diseases such as venous thrombosis and ischemic stroke, and its sensitivity is higher than that of simple D-dimer.…”
Section: Introductionmentioning
confidence: 99%